THE INFLUENCE OF THE INTERNET ON ETHICS AND MORALS OF CLASS X STUDENTS OF SMK DARUL ANWAR SINGOJUURUH, BANYUWANGI REGENCY, EAST JAVA PROVINCE, INDONESIA - arie Ramadhani (International Jurnal of Education Schoolars, 2020)
This study discusses the use of the internet for class X students of SMK Darul Anwar Singojuruh Banyuwangi Regency. The method used in this study is a qualitative analysis of product moment assessment techniques. Participation in this study was grade X students who helped 341 students. The sample used in this study was a 34 student experiment. The sampling technique used purposive sampling. The instruments needed in this study were questionnaire sheets. This research variable is divided into two, namely the independent variable X (internet use) and the Y variable (moral). Based on the results of this study show the calculation results when the product obtained by rxy of 0.069. If the score is compared in the table with the number of respondents 34 in the r table shows 0.329, so the coefficient of difficulty is unnecessary between the use of the internet with the students' morals because between t results are smaller than t tables. then there is no difference between the use of the internet against moral students with very low categories at intervals of 0.00-0.199